Investigating Factors Affecting Entrepreneurship Development in Botswana - Radikoko, Ishmael; Maswabi, Baagi; Dzimiri, Mashoko (Archives of Business Research, 2015)
This study was conducted in order to explore the factors that affect entrepreneurship development in Botswana. Furthermore, it went on to investigate if there is any relationship between education and entrepreneurial success. Lastly the paper investigates problems and some of the barriers that hinder potential entrepreneurs from engaging in new venture creation or enhancement of existing businesses. The data used for this research was collected through the use of questionnaire which was distributed to respondents in the two most populated cities of Botswana being Gaborone and Francistown. The results shows that the main factors that affect entrepreneurial development in Botswana are, Research and Development; Education & Training; Government Entrepreneurial programs and Government Policies which are all found to constrain entrepreneurship development because they are lacking in terms of advancing entrepreneurial activity in Botswana. The results further show that there is no strong relationship between education and entrepreneurship development. Lastly the results of this study show that bureaucracy and ineffective implementation of government policies stifles entrepreneurial development. We recommend that the government should review its policies meant to enhance entrepreneurial activity because to date they have been found to be ineffective. Further, the education system especially targeted at entrepreneurial development has to be revamped to align it to the ones observed in successful nations across the globe. Lastly bureaucracies in govern structures that are meant to enhances entrepreneurial development has to be minimized.